Robots, Meaning, and Self-Determination - Milena Nikolova; Femke Cnossen; Boris Nikolaev (Institute of Labor Economics (IZA), 2023)
This paper is the first to examine the impact of robotization on work meaningfulness and autonomy, competence, and relatedness, which are essential to motivation and well-being at work. Drawing on surveys from workers and industry-specific robotization data across 14 industries in 20 European countries from 2005 to 2021, our analysis reveals a consistent negative impact of robotization on perceived work meaningfulness and autonomy. Using instrumental variables, we find that doubling robotization correlates with a 0.9% decrease in work meaningfulness and a 1% decrease in autonomy. To put this in perspective, aligning the robotization intensity of the top five industry with the leading industry's robotization level in 2020—which would mean a 7.5-fold increase—would lead to a 6.8% reduction in work meaningfulness and a 7.5% reduction in autonomy. The link between robotization, competence, and relatedness is also negative but less robust. We also examine how tasks, skills, and socio-demographic characteristics moderate the relationship. We find that workers with routine tasks drive the negative effects of robotization on autonomy. However, we also discover that engaging in social tasks and utilizing computers as tools for independent work can help workers maintain a sense of autonomy in industries and job roles that adopt robots. Our results highlight that by deteriorating work meaningfulness and self-determination, robotization can impact work life above and beyond its consequences for employment and wages.
Keywords: J01; J30; J32; J81; I30; I31; M50; 330; work meaningfulness; self-determination theory; robotization; automation